Steig, W., (2021). "El gran viaje de Dominic." Traductora: Rovira Gemma, Blackie Books, 167 pp - Escrig Aparicio, José Antonio (Ondina - Ondine, 2022)
DOMINIC, DE WILLIAM STEIG: EL CAMINO DE LA AVENTURAReseña de José Antonio Escrig Aparicio,  Steig, W., (2021). El gran viaje de Dominic. Traductora: Rovira Gemma, Blackie Books, 167 pp.